Fetal mitochondrial DNA in maternal plasma in surrogate pregnancies: Detection and topology. (12th November 2020) - Ma, Mary‐Jane L.; Yakovenko, Sergey; Zhang, Haiqiang; Cheng, Suk Hang; Apryshko, Valentina; Zhavoronkov, Alex; Jiang, Peiyong; Chan, K. C. Allen; Chiu, Rossa W. K.; Lo, Y. M. Dennis
Abstract: Objectives: Due to the maternally‐inherited nature of mitochondrial DNA (mtDNA), there is a lack of information regarding fetal mtDNA in the plasma of pregnant women. We aim to explore the presence and topologic forms of circulating fetal and maternal mtDNA molecules in surrogate pregnancies. Methods: Genotypic differences between fetal and surrogate maternal mtDNA were used to identify the fetal and maternal mtDNA molecules in plasma. Plasma samples were obtained from the surrogate pregnant mothers. Using cleavage‐end signatures of Bfa I restriction enzyme, linear and circular mtDNA molecules in maternal plasma could be differentiated. Results: Fetal‐derived mtDNA molecules were mainly linear (median: 88%; range: 80%–96%), whereas approximately half of the maternal‐derived mtDNA molecules were circular (median: 51%; range: 42%–60%). The fetal DNA fraction of linear mtDNA was lower (median absolute difference: 9.8%; range: 1.1%–27%) than that of nuclear DNA (median: 20%; range: 9.7%–35%). The fetal‐derived linear mtDNA molecules were shorter than the maternal‐derived ones. Conclusion: Fetal mtDNA is present in maternal plasma, and consists mainly of linear molecules. Surrogate pregnancies represent a valuable clinical scenario for exploring the biology and potential clinical applications of circulating mtDNA, for example, for pregnancies conceived following mitochondrial replacement therapy.